PENGGUNAAN MEDIA PEMBELAJARAN MINIATUR TATA SURYA UNTUK MENINGKATKAN HASIL BELAJAR SISWA DI KELAS VI MATERI SISTEM TATA SURYA UPTD SD INPRES OEBA 1 - Juan Abineno; Maxel Koro; Kurniayu T. R. A. Ratu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research aims to improve student learning outcomes through the use of solar system miniature learning media on solar system materials. This research is motivated by the low learning outcomes of grade VI students of UPTD Elementary School Inpres Oeba 1 Kupang City. The low learning outcomes are caused by the learning process that is still dominated by teachers, the use of less interactive media, and the low involvement of students in learning activities. As a result, students tend to be passive, lack focus, and have difficulty understanding abstract concepts of the solar system. This study uses the Classroom Action Research (PTK) method which is carried out in two cycles, where each cycle consists of the stages of planning, implementation of actions, observation, and reflection. The subject of the study was 18 students in grade VI UPTD SD Inpres Oeba 1. The data collection technique is carried out through observation sheets of teacher and student activities and learning outcome tests. The data obtained were analyzed descriptively, quantitatively, and qualitatively. The results of the study showed that in the first cycle the number of students who achieved learning completeness was still low, namely 8 students (44.44%), while 10 students (55.56%) had not completed due to lack of concentration and active participation in learning. In cycle II, student learning outcomes experienced a significant increase, where as many as 16 students (88.89%) achieved learning completion. The increase is supported by increased activity, motivation, concentration, and cooperation of students in groups through the use of miniature solar system media. Meanwhile, students who have not completed are given guidance and enrichment. Thus, the use of solar system miniature learning media has been proven to have a positive impact on improving student learning outcomes, as shown by the increase in learning completeness from cycle I to cycle II.